Influence of Family Background on Islamic Entrepreneurial Skills among Students in Aceh’s Islamic Higher Education Institutions - Lailatussaadah, Lailatussaadah; Jamil, Asyraf Isyraqi Bin; Rekan, Abd Aziz; Hayati, Salma; Nurmayuli, Nurmayuli (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study investigates the impact of family background on Islamic entrepreneurial competencies among students in Aceh’s Islamic higher education institutions. Utilizing a quantitative survey, the research explores key variables such as the occupational backgrounds of both parents. The findings reveal two significant factors influencing students’ Islamic entrepreneurial competencies: the occupational backgrounds of their fathers and mothers. However, the mother’s influence is more prominent, particularly in shaping students’ psychomotor competencies, while no significant effect was found on cognitive and affective domains. The study highlights the need to incorporate family influences into the broader framework of entrepreneurial education in Islamic institutions. It suggests that educational policies should not only focus on skill development but also engage families actively in the learning process. By integrating family support, these institutions can empower students to leverage their backgrounds, fostering both economic and spiritual development within the community.